"Laws of Fear" in the EU: The Precautionary Principle and Public Health Restrictions to Free Movement of Persons in the Time of COVID-19. (5th March 2023) - GOLDNER LANG, Iris
Abstract : COVID-19 has demonstrated the fragility of EU free movement rules when we are faced with an unknown virus of such magnitude and strength that it threatens our lives, health systems, economies and society. The aim of this text is to show the dynamics between the threat of COVID-19 and the rules imposed as a response to the pandemic, which have impacted the functioning of the EU internal market and the Schengen area. The text will concentrate on the application of the precautionary principle and public health restrictions, caused by COVID-19, to free movement of persons in the EU. The analysis will lead to three conclusions. First, it will be shown that the decisions to apply free movement restrictions and the logic followed in the EU COVID-19-related documents can be viewed as a triumph of the precautionary principle. Second, it will be argued that implementing the precautionary principle has a transformative effect on the application of the principle of proportionality in EU law. Finally, it will be shown that COVID-19 has emphasised and increased the difference between the conditions for the applicability of public health restrictions when compared to restrictions based on public policy and public security grounds.